PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY SMP KELAS 9 PADA MATERI MALWARE - Rizky Rahmad Andre Anang; Gres Dyah Kusuma Ningrum; Hikmatul Afifah Fikriati (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2025)
This research aims to develop learning media that apply augmented reality (AR) in grade 9 informatics subjects with malware material. The background of this research is based on students' needs for creative and theological learning tools to improve understanding of abstract or difficult-to-understand concepts in the digital world. With the ADDIE development approach which includes several stages, namely analysis, design, development, implementation, and evaluation. Validation from material experts, media experts and users provides the fact that the results are very valid. Student trials showed an increase in interest in learning and understanding of malware material. This media provides an interesting and contextual learning experience by displaying 3D illustrations of various types of malware through AR-based smartphones. Therefore, the use of AR in this learning media has potential as an alternative solution in supporting effective and interactive learning activities at the junior high school level.